Workshop Perancangan Pembelajaran Matematika Berbasis Teknologi (Geogebra) bagi Guru-Guru Sekolah Dasar di Kecamatan Tambang - Zetra Hainul Putra; Intan Kartika Sari; Jesi Alexander Alim; Gustimal Witri; Syahrilfuddin Syahrilfuddin; Muhammad Fendrik; Dede Permana; Zariul Antosa; Muhammad Abdul Pangestu (Journal of Community Engagement Research for Sustainability, 2022)
The government's policy for implementing distance learning or online learning has been implemented for approximately a year to prevent the transmission/spread of the coronavirus. For about a year, teachers at every level of education have tried to optimize learning by utilizing digital technology. Teachers who previously had not been able to use technology were forced to be literate and up to date with technology to facilitate the learning process. However, teachers encounter several obstacles during distance learning, and there are still many teachers who do not understand how to design technology-based media and teaching materials for learning mathematics. Moving on from this problem, the PGSD service team in mathematics designed a technology-based mathematics learning design workshop (GeoGebra) for elementary school teachers. This workshop held three meetings with a blended learning model (online-offline-online) at SDN 024 Tarai Bangun. The workshop was attended by 22 elementary school teachers from 3 elementary schools. The workshop results showed that teachers experienced an increase in knowledge and skills, especially in designing GeoGebra-based mathematics learning from the less to average category. This activity implies that teachers are expected to implement the knowledge and skills acquired in learning mathematics in the classroom.